Scientific identity and epistemology of movement, exercise, and sport sciences through the analysis of scientific production of Italian full professors - D’Isanto, Tiziana; Esposito, Giovanni; Altavilla, Gaetano; D’Elia, Francesca; Raiola, Gaetano (Frontiers in Education, 2024)
This study addresses the epistemological and identity challenges encountered by Movement, Exercise, and Sport Sciences (MEaSS) in Italy, particularly concerning the organization of scientific knowledge within academic contexts. MEaSS struggles to define its scientific identity and address epistemological concerns due to the concurrent operation of its academic scientific disciplines (ASD) within both biomedical and pedagogical domains. This situation raises questions about the classification of knowledge within MEaSS and its distinctiveness within the Italian academic community. The study aims to analyze the scientific production of Italian full professors in two ASDs of MEaSS and determine its relevance to biomedical, pedagogical, psychological, or sports domains. It also intends to investigate the alignment of Italian academic structures with international standards, particularly the European Research Council (ERC) model. Each full professor's top twenty scientific products, ranked by the highest number of citations within the Google Scholar database, were analyzed. The analysis of scientific production among Italian full professors in the two ASDs of Movement, Exercise, and Sport Sciences (MEaSS) revealed significant findings. In the ASD of M-EDF/01, 58.5% of publications were attributed to the biomedical domain, followed by 32.7% in the sports domain, 6.9% in the pedagogical domain, and 1.9% in the psychological domain. For the ASD of M-EDF/02, 47.5% of publications were in the biomedical domain, 25% in the sports domain, 18.1% in the pedagogical domain, and 9.4% in the psychological domain. The prevalence of biomedical-focused research within both ASDs of MEaSS highlights a notable deviation from the intended disciplinary boundaries, raising concerns regarding the loss of scientific identity and epistemological coherence. These results emphasize the urgent need for alignment with international standards to ensure clarity of scientific identity and promote interdisciplinary research in MEaSS.